Mentorship to strengthen health system leadership: A case study of the Walungu rural health zone in the eastern Democratic Republic of Congo. - Rosine Bigirinama; Ghislain Bisimwa; Samuel Makali; Aimé Cikomola; Janvier Barhobagayana; Jean-Corneille Lembebu; Christian Chiribagula; Pacifique Mwene-Batu; Abdon Mukalay; Denis Porignon; Albert Tambwe (PLOS Global Public Health)
From 2015 to 2019, the "RIPSEC" program launched a mentorship program, transforming the Walungu health zone, in eastern crisis-affected Democratic Republic of Congo, into a "Learning and Research Zone" (LRZ). As part of the program, a local university was tasked with strengthening the LRZ manager's leadership capacities, including efforts to troubleshoot challenges related to the proliferation of informal healthcare facilities (IHFs). IHFs are unregulated healthcare structures operating on the fringes of the law, and claiming to offer cheaper, higher-quality care to the local population. This study evaluates the impact of RIPSEC mentorship on leadership development and the performance in the Walungu LRZ, particularly concerning the utilization of integrated curative health services in competition with IHFs. We used a mixed method approach, combining retrospective analysis of some key health indicators before (2014) and during RIPSEC program (2014 vs. 2015-2019), and in-depth qualitative interviews with members of the LRZ management team. Quantitative data were presented as frequencies and proportions. Simple linear regression (p<0.05) measured the influence of IHFs on service use. The LRZ's functionality and performance were assessed using an internal benchmarking approach, with results presented as trend curves. Deductive analysis of interviews allowed for a deeper exploration of quantitative trends. Despite efforts by the LRZ managers to regulate IHFs, these structures negatively impact the use of curative services by diverting patients away from integrated healthcare options. RIPSEC mentorship notably enhanced manager's leadership skills, leading to more effective management. While the use of curative health services slightly increased during the program, rates remained below 50%, and gains were not sustained post-program. RIPSEC mentorship has positively impacted leadership and performance in Walungu. However, financial challenges and the persistent influence of IHFs continue to impede the sustainability of these gains. Comprehensive strategies beyond enhancing managerial leadership solely, are necessary.